Advantages of using New Information Technologies in Insurance Activities (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the advantages of using modern information technologies in insurance activities. In particular, it covers aspects such as automation of insurance services through digital transformation processes, artificial intelligence, blockchain, cloud technologies and mobile applications, improving the quality of customer service, expanding the possibilities of risk analysis and control. Also, using the example of the insurance market of Uzbekistan, practical examples are shown to show how the introduction of information technologies affects efficiency. The article provides conclusions and recommendations on the role of technological innovations in the development of the insurance system and promising directions.